Analysis of grounding systems for electric traction. - Natarajan, R. (IEEE Transactions on power delivery)
The traction power supply system consists of the feeder, trolley, rails and static conductors. The traction load is applied between the trolley and rails as a single phase load. In order to maintain near constant voltage along the traction-route, the paralleling stations are equipped with auto-transformers along the track. Further, there are structures such as bridges and platforms along the traction route. The substation and the paralleling stations are provided with grounding grids, which are in turn connected to the static wires. The bridge and the platform grounds are connected to the rails or static wires. The rails and the static wires are connected at certain locations to provide continuity of the return system. The grounding system along the entire power system is designed so that safety of personnel and passengers is assured. The performance of the grounding system is assessed by analysis of the integrated power and grounding system. The maximum touch voltages at different locations are computed and compared with the IEEE Standard 80 values to ensure safety